2013
DOI: 10.5539/jas.v5n2p24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Forage Type Barley Varieties for Forage Yield and Nutritive Value in the Peace Region of Alberta

Abstract: There is increasing use of barley (Hordeum vulgare L.) forage for swath grazing, bale grazing and silage for back grounding and finishing beef cattle in western Canada. Twelve barley varieties (6 two row and 6 six row) were compared in field trials in the Peace Region of Alberta, from 2009 to 2011, to identify the varieties with superior forage yield and nutritive value. Forage yield dry matter (DM) yield was greatest for Busby, followed by Ponoka, CDC Cowboy, Seebe, CDC Austenson, Vivar, Chigwell, Sundre, Xen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
27
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 13 publications
10
27
0
4
Order By: Relevance
“…The lack of significant effect of oat varieties on forage CP in this study is similar to the findings on a set of barley varieties tested on same sites (Gill et al, 2013) and a different set of oat varieties tested in a different environment (Habib et al, 2003). Our findings, however, differ from those of Kibite et al (2002b), who observed higher CP values (ranging from 11.9-13.8% CP) and significant difference in CP among oat varieties.…”
Section: Cp and Cp Fractionssupporting
confidence: 77%
See 2 more Smart Citations
“…The lack of significant effect of oat varieties on forage CP in this study is similar to the findings on a set of barley varieties tested on same sites (Gill et al, 2013) and a different set of oat varieties tested in a different environment (Habib et al, 2003). Our findings, however, differ from those of Kibite et al (2002b), who observed higher CP values (ranging from 11.9-13.8% CP) and significant difference in CP among oat varieties.…”
Section: Cp and Cp Fractionssupporting
confidence: 77%
“…The lower CP values in the present study and those of barley (Gill et al, 2013) compared to other locations could be as a result of differences in soil type, crop management practices and weather. In both the present study and Gill et al (2013), the effect of weather is indicated by a tendency of higher CP average in drier year of 2010 compared to the 2009 and 2011. Reduced forage CP with higher DM in 2009 and 2011 is thought to have been a result of dilution effect.…”
Section: Cp and Cp Fractionsmentioning
confidence: 57%
See 1 more Smart Citation
“…Along with DMY, CP concentration in the forage is the key factor to determine winter feed value (Gill et al, 2013b). The two key factors could be represented by CPY.…”
Section: Discussionmentioning
confidence: 99%
“…To improve annual cereal and legume forages utilization as hay, green feed or silage and to develop supplementation programs for forage-based nutrition, it is important to know how the nutritional values of different forages match up with beef cow needs. Studies to identify promising barley (Gill et al, 2013a) oat (Gill et al, 2013b), and triticale (Gill & Omokanye, 2016) varieties for beef cattle production systems have been conducted in the PC region of Alberta. The objectives of this study were to compare the intercrops of spring oat, barley and triticale with pea varieties to respective cereal monocrops grown in the north western (PC) Alberta, Canada; in terms of their forage yield, and feed quality.…”
Section: Introductionmentioning
confidence: 99%